Amnesia and its relation with concession (Rukhsah) on performing prayer (Solah) - Abdul Ghani, Radiah; Ariaff, Muhammad Ammar Adli; Che Mohamad, Che Anuar; Ikmal Hisham, Ahmad Irfan (UPM Press, 2019)
The low percentage of in-ward patients that performing solah during their stay in hospital indicatess a worrying trend attributed to the minimal knowledge of rukhsah for solah during certain illness. Among the illness which could affect the ability of a Muslim to perform their act of worship is a memory disorder known as amnesia. There are several types of amnesia and classification where each of them manifest different level of severity. The different level of severity requires level of of rukhsah in solah. This review was conducted based on narrative review framework and integrated with Islamic Perspective by framework analysis. In relation to that, the distinction between ‘aqil and ghairu ‘aqil person is identified where transient global amnesia is suggested as ‘aqil person meanwhile the Korsakoff’s syndrome and global psychogenic amnesia is suggested as the ghairu ‘aqil person. For a person who is regarded as ghairu ‘aqil, the obligation of solah is accrued and they are not required to qada’ the solah after memory disorder is preserved. As part of the concession to the Muslim amnesic patient, they are permitted to perform the solah in jama’. In conclusion, the severity of the amnesic syndrome varies based on their classifications and the practice of rukhsah on solah should be in accordance to the principles of rukhsoh.